Circular RNA and intervertebral disc degeneration: unravelling mechanisms and implications - Xie, Guohao; Wu, Tingrui; Ji, Guangju; Wu, Hang; Lai, Yue; Wei, Bo; Huang, Wenhua (Frontiers in Molecular Biosciences, 2023)
Low back pain (LBP) is a major public health problem worldwide and a significant health and economic burden. Intervertebral disc degeneration (IDD) is the reason for LBP. However, we have not identified effective therapeutic strategies to address this challenge. With accumulating knowledge on the role of circular RNAs in the pathogenesis of IDD, we realised that circular RNAs (circRNAs) may have tremendous therapeutic potential and clinical application prospects in this field. This review presents an overview of the current understanding of characteristics, classification, biogenesis,